Symptoms of mineral deficiency in Pterocarpus indicus willd. seedlings - Srivastava, P. B. L. (Forestry Department Peninsular Malaysia, 1979)
This paper describes the effect of macro-nutrient deficiencies on the growth and morphology of Pterocarpus indicus Willd, seedlings. The lack of various nutrients resulted in prominent dificiency symptoms. Severe chlorosis of leaves and poor shoot and root development was observed due to N and P deficiencies. Lack of Ca and S resulted in die-back of leader shoot and root. In contrast, K deficiency did not result in severe morphological symptoms.